Temporomandibular joint ankylosis caused by systemic (distal) infection: a case report and literature review - Yuan, Shi-qing; Dong, Rui; Li, Tian-zhong; Hu, Min; Liang, Li-min; Ma, Jun-li; Tao, Ye (Shanghai kou qiang yi xue, 2014)
There were many causes for temporomandibular joint (TMJ) ankylosis including infection, trauma, degenerative changes and space-occupying lesion. This article reported a case of bilateral TMJ ankylosis caused by systemic (distal) infection. A 35-year old female patient complained of difficulty of opening mouth for about 20 years. She developed abscess in several places all over the body including bilateral TMJ 20 years ago. CT indicated that the condylar process was fused with the temporal bone. The patient was treated with resection of bilateral condylar/coracoid process and total joint prosthesis replacement. The maximal incisal opening was 2.5 cm 3 months post operation. The patient obtained a satisfied function of eating and speaking.